Private Rome [large type] - Patterson, James, 1947-; Hamdy, Adam, 1974- (Patterson, James, 1947- Private novels, 2026)
"For centuries, seekers have come to the Vatican for answers. Now Private Rome is asking the questions. Jack Morgan, ex-Marine helicopter pilot and CIA agent, is in Italy to open the latest outpost of his international private investigation firm. Their wealthy client base demands maximum force and maximum discretion. But when a priest is murdered at the firm's opening party, Morgan and Matteo Ricci--a decorated Rome police inspector, and Morgan's newly appointed deputy come under intense scrutiny. As Morgan and Ricci work the case, they discover that eight priests have died, all under watch of the Swiss Guard and the Vatican Police. Private relies on the world's most advanced forensic tools to make and break cases. This one rests on breaking the secret hold of the Holy See's all-powerful, all knowing inner circle."--